Antimicrobial Susceptibility and Genomic Analysis of Aliarcobacter cibarius and Aliarcobacter thereius, Two Rarely Detected Aliarcobacter Species - Hänel, Ingrid; Müller, Eva; Santamarina, Belén González; Tomaso, Herbert; Hotzel, Helmut; Busch, Anne (Frontiers in Cellular and Infection Microbiology, 2021)
Aliarcobacter cibarius and Aliarcobacter thereius are two rarely detected Aliarcobacter species. In the study, we analyzed the antimicrobial susceptibility and provide detailed insights into the genotype and phylogeny of both species using whole-genome sequencing. Thermophilic Campylobacter species are the most common bacterial foodborne pathogens causing gastroenteritis in humans worldwide. The genus Aliarcobacter is part of the Campylobacteraceae family and includes the species Aliarcobacter butzleri, Aliarcobacter cryaerophilus, Aliarcobacter skirrowii, and the rarely described Aliarcobacter cibarius, Aliarcobacter faecis, Aliarcobacter lanthieri, Aliarcobacter thereius, and Acrobarter trophiarum. Aliarcobacter are emergent enteropathogens and potential zoonotic agents. Here, we generated, analyzed, and characterized whole-genome sequences of Aliarcobacter cibarius and Aliarcobacter thereius. They were isolated from water poultry farms in Germany, cultured and identified by MALDI-TOF MS. With PCR the identity was verified. Antibiotic susceptibility testing was carried out with erythromycin, ciprofloxacin, doxycycline, tetracycline, gentamicin, streptomycin, ampicillin, and cefotaxime using the gradient strip method (E-test). Whole-genome sequences were generated including those of reference strains. Complete genomes for six selected strains are reported. These provide detailed insights into the genotype. With these, we predicted in silico known AMR genes, virulence-associated genes, and plasmid replicons. Phenotypic analysis of resistance showed differences between the presence of resistance genes and the prediction of phenotypic resistance profiles. In Aliarcobacter butzleri, the nucleotide sequence of the gyrA gene (DQ464331) can show a signature mutation resulting in an amino acid change T85>I. Acrobarter cibarius and Acrobarter thereius showed the same gene as assessed by similarity annotation of the mutations 254C>G. Most of the isolates were found to be sensitive to ciprofloxacin. The ciprofloxacin-resistant Aliarcobacter thereius isolate was associated with the amino acid change T85>I. But this was not predicted with antibiotic resistance databases, before. Ultimately, a phylogenetic analysis was done to facilitate in future outbreak analysis.